Fell Muir Lecture: Collagen fibril formation in vitro and in vivo. Issue 1 (16th May 2017) - Kadler, Karl E.
Summary: It is a great honour to be awarded the Fell Muir Prize for 2016 by the British Society of Matrix Biology. As recipient of the prize, I am taking the opportunity to write a minireview on collagen fibrillogenesis, which has been the focus of my research for 33 years. This is the process by which triple helical collagen molecules assemble into centimetre‐long fibrils in the extracellular matrix of animals. The fibrils appeared a billion years ago at the dawn of multicellular animal life as the primary scaffold for tissue morphogenesis. The fibrils occur in exquisite three‐dimensional architectures that match the physical demands of tissues, for example orthogonal lattices in cornea, basket weaves in skin and blood vessels, and parallel bundles in tendon, ligament and nerves. The question of how collagen fibrils are formed was posed at the end of the nineteenth century. Since then, we have learned about the structure of DNA and the peptide bond, understood how plants capture the sun's energy, cloned animals, discovered antibiotics and found ways of editing our genome in the pursuit of new cures for diseases. However, how cells generate tissues from collagen fibrils remains one of the big unsolved mysteries in biology. In this review, I will give a personal account of the topic and highlight some of the approaches that my research group are taking to find new insights.